Amazing maize in Malawi: Input subsidies, factor productivity and land use intensification - Stein Holden (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2013)
The paper uses three years of household farm plot panel data (2006-2009), covering six districts in central and southern Malawi to assess factor productivity and farming system development under the input subsidy program. All farm plots of the households were measured with GPS. Maize production intensified in this period as maize area shares of the total farm size were reduced while input use intensity and yields increased. Yields of improved maize were significantly (+323 kg/ha) higher than for local maize. Improved maize seeds were used on only half of the maize plots that received subsidized fertilizer causing fertilizer use inefficiency.
Keywords: Q16; Q18; 330; Maize; Malawi; improved varieties; input subsidies; fertilizer use efficiency; land productivity; farming system changes